Smoking Risk Factors Against Hypertension Incidence in Pre-Elderly in the Work Area of the Minasaupa Health Center Makassar City - Hatta, Nurul Zafirah; Bustan, Najib; Arman, Arman (Journal of Aafiyah Health Research (JAHR), 2022)
Background: Hypertension is a health problem that is quite dangerous worldwide because hypertension is a major risk factor that leads to cardiovascular diseases such as heart attack, heart failure, stroke and kidney disease, where in 2016 ischemic heart disease and stroke became the two main causes of death in Indonesia. world. Aim: The purpose of this study was to analyze the risk factors of smoking on the incidence of hypertension in pre-elderly in the working area of ​​the Minasa Upa Public Health Center. Method: The design of this study used a case-control study, namely 44 pre-elderly hypertension cases and 44 non-hypertensive pre-elderly controls carried out in the working area of ​​the Minasa Upa Health Center Makassar City. The research data was collected by observing and interviewing respondents using a questionnaire. Data analysis was carried out by univariate analysis, bivariate using chi-square test and calculation of Odds Ratio (OR), multivariate analysis using multiple logistic regression test. Results: There was an influence of smoking risk factors (OR=3.3), occupation (OR=2.7), stress (OR= 2.9) on the incidence of hypertension. And the dominant variable is smoking (OR adjusted 3.3). Conclusion: Smoking, work, and stress are factors that influence hypertension. It is hoped that the puskesmas will further increase the participation of Posbindu in reducing risk factors for hypertension, such as counseling, making joint sports activities and creating smoke-free areas.